Shared versus private mobility: Modeling public interest in autonomous vehicles accounting for latent attitudes. (December 2018) - Nazari, Fatemeh; Noruzoliaee, Mohamadhossein; Mohammadian, Abolfazl (Kouros)
Highlights: Elicits public interest in private and shared autonomous vehicles (AVs). Considers carsharing, ridesourcing, and ridesharing with AVs. Models latent subjective attitudes towards AV safety concern. Finds highly positively correlated private and shared AV outcomes. Offers policies to promote public interest in AVs. Abstract: Emerging autonomous vehicles (AVs) and shared mobility systems per se will transform urban passenger transportation. Coupled together, shared AVs (SAVs) can facilitate widespread use of shared mobility services by providing flexible public travel modes comparable to private AV. Hence, it may be conjectured that future urban mobility is likely an on-demand service and AV private ownership is unappealing. Nonetheless, it is still unclear what observable and latent factors will drive public interest in (S)AVs, the answer to which will have important implications on transportation system performance. This paper aims to jointly model public interest in private AVs and multiple SAV configurations (carsharing, ridesourcing, ridesharing, and access/egress mode) in daily and commute travels with explicit treatment of the correlations across the (S)AV types. To this end, multivariate ordered outcome models with latent variables are employed, whereby latent attitudes and preferences describing traveler safety concern about AV, green travel pattern, and mobility-on-demand savviness are accounted for using structural and measurement equations. Drawing from a stated preference survey in the State of Washington, important insights are gained into the potential user groups based on the socio-economic, built environment, and daily/commute travel behavior attributes. Key policies are also offered to promote public interest in (S)AVs by scrutinizing the marginal effects of the latent variables.